Magnetic hydrogel microspheres as well as preparation method and application thereof

By adopting a core-shell structure magnetic material and a hydrogel structure with a spiral structure magnetic material and a hydrogel, the problems of degradation of magnetic hydrogel microspheres in the non-target area and recovery of magnetic materials in the prior art are solved, and precise cell delivery and efficient recovery of magnetic materials are achieved.

CN119770649APending Publication Date: 2025-04-08SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411738428.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The degradation of existing magnetic hydrogel microspheres in non-target areas causes cells to fail to achieve accurate release and the recovery of magnetic materials is difficult.

Method used

Magnetic hydrogel microspheres with a spiral structure and a hydrogel that completely coats it form a core-shell structure. The magnetic hydrogel microspheres are accurately navigated and positioned in the body by applying a magnetic field, and the recovery of magnetic materials is achieved after the hydrogel is degraded.

Benefits of technology

The precise movement of magnetic hydrogel microspheres under the external magnetic field and the precise release of target areas are achieved, which improves the accuracy of cell delivery and reduces biosafety risks through the recycling of magnetic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770649A_ABST
    Figure CN119770649A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biopolymer materials, and particularly discloses magnetic hydrogel microspheres as well as a preparation method and application thereof. The magnetic hydrogel microspheres comprise hydrogel and a magnetic material, the hydrogel is spherical or spheroid, the magnetic material is of a spiral structure, the hydrogel and the magnetic material form a core-shell structure, and the magnetic material is completely coated with the hydrogel. According to the magnetic hydrogel microsphere, the core-shell structure is composed of the internal magnetic material with the spiral structure and the external hydrogel, when the magnetic hydrogel microsphere is used for targeted transportation, the magnetic material with the spiral structure has better hydrodynamic characteristics, the magnetic hydrogel microsphere is moved to a target area under the action of an external magnetic field, and the magnetic hydrogel microsphere can be used for targeted transportation. The hydrogel is degraded in a target area, carried effective components are accurately released, the magnetic material moves to a designated position under the action of an external magnetic field to be recycled, targeted transportation is completed, meanwhile, long-term residue of the magnetic material in the body is avoided, and potential biological safety risks are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biopolymer materials, and in particular to a magnetic hydrogel microsphere and a preparation method and application thereof. Background Art

[0002] With the development of microfluidic technology, microstructured materials manufactured based on microfluidic systems have shown great potential in the biomedical field. Among them, magnetic hydrogel microspheres have attracted widespread attention due to their application prospects in drug delivery, cell delivery, tissue engineering and other fields. In these applications, cell delivery is a very challenging task. Magnetic hydrogel microspheres provide an attractive solution in this field: magnetic hydrogel microspheres used for cell delivery are usually core-shell microspheres, composed of a material with magnetic responsiveness (core) and a biocompatible hydrogel material (shell). Cells are carried by biocompatible hydrogel materials, and their movement and positioning are controlled by the response characteristics of magnetic materials. After the hydrogel material is degraded, the cells loaded on the magnetic hydrogel microspheres are accurately released to the target area.

[0003] However, the biocompatible hydrogel materials used in the existing magnetic hydrogel microspheres prepared by microfluidics may degrade in non-target areas, resulting in the inability to accurately release cells. In addition, the structure of the materials with magnetic response performance is relatively simple, and may not produce sufficient movement or response to the magnetic field, affecting the recovery effect. Therefore, the existing technology needs to be improved. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a magnetic hydrogel microsphere and a preparation method and application thereof, aiming to solve the problem that the existing magnetic hydrogel microspheres cannot achieve precise release and the magnetic material therein is difficult to recover.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect of the present application, a magnetic hydrogel microsphere is provided, wherein the magnetic hydrogel microsphere comprises: a hydrogel and a magnetic material, wherein the hydrogel is in a sphere or an ellipsoid, and the magnetic material is in a spiral structure, the hydrogel and the magnetic material form a core-shell structure, and the hydrogel completely covers the magnetic material.

[0007] Optionally, the hydrogel comprises at least one of gelatin methacrylated gelatin, polyethylene glycol diacrylate, polyethylene glycol diacrylamide, and hyaluronic acid methacrylate.

[0008] Optionally, the magnetic material includes at least one of metal oxide nanoparticles and magnetic polymers; the metal oxide nanoparticles include at least one of ferrosoferric oxide nanoparticles, cobalt oxide nanoparticles, and manganese oxide nanoparticles.

[0009] The second aspect of the present application provides a method for preparing the magnetic hydrogel microspheres of the first aspect of the present application, comprising the steps of: providing a core layer solution, a shell layer solution and an oil phase solution, wherein the core layer solution comprises a magnetic material, and the shell layer solution comprises a hydrogel; respectively injecting the core layer solution, the shell layer solution and the oil phase solution into different flow channels of a coaxial flow microfluidic device, wherein the core layer solution, the shell layer solution and the oil phase solution converge at the liquid outlet of the coaxial flow microfluidic device to obtain monomer droplets, and using ultraviolet light to cure the monomer droplets to obtain the magnetic hydrogel microspheres.

[0010] Optionally, the core layer solution includes, by mass percentage, 1-2% sodium cellulose, 1-5% polyethylene glycol diacrylate, 0.1-0.3% photoinitiator and 1.5-3% magnetic material; the shell layer solution includes, by mass percentage, 5-10% hydrogel, 0.3-0.5% sodium cellulose and 0.2-0.4% photoinitiator; the oil phase solution includes at least one of mineral oil, silicone oil, liquid paraffin, fluorinated oil, olive oil, corn oil and soybean oil.

[0011] Optionally, the photoinitiator includes at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphate, Irgacure 2959, and riboflavin.

[0012] Optionally, the core layer solution, shell layer solution and oil phase solution are respectively injected into different flow channels of the coaxial flow microfluidic device, the injection flow rate of the core layer solution is 2-10 μL / min, the injection flow rate of the shell layer solution is 6-20 μL / min, and the injection flow rate of the oil phase solution is 0.6-2.5 mL / min.

[0013] Optionally, the UV curing has an UV irradiation intensity of 60-110 mW / cm 2 .

[0014] The third aspect of the present application provides a use of the magnetic hydrogel microspheres according to the first aspect of the present application in the preparation of targeted transport products.

[0015] Optionally, the targeted transport product is used to transport cells or drugs.

[0016] Beneficial effects of the present application: The magnetic hydrogel microspheres in the present application have a core-shell structure composed of an internal magnetic material with a helical structure and an external hydrogel. The hydrogel has good biocompatibility and degradability and can be degraded in vivo. The magnetic material with a helical structure has better fluid dynamics properties, can effectively overcome fluid resistance through rotational motion, and generate effective torque or propulsion under an external magnetic field, so that the magnetic hydrogel microspheres can be more accurately oriented and navigated under an external magnetic field, thereby enabling the magnetic hydrogel microspheres to move to the target area more efficiently. At the same time, the magnetic material with a helical structure is also conducive to the recovery of the magnetic material after the hydrogel is degraded. In addition, the magnetic material is completely coated by the hydrogel to avoid the potential retention of the magnetic material and reduce the potential biosafety risk of the magnetic hydrogel microspheres. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for describing the embodiments are briefly introduced below.

[0018] Figure 1 An optical microscope image of the magnetic hydrogel microspheres provided in the embodiments of the present application;

[0019] Figure 2 A flow chart of a method for preparing magnetic hydrogel microspheres provided in an embodiment of the present application;

[0020] Figure 3 A schematic diagram of the structure of a device for preparing magnetic hydrogel microspheres provided in an embodiment of the present application;

[0021] Figure 4 A schematic diagram of the use of magnetic hydrogel microspheres for cell delivery provided in an embodiment of the present application;

[0022] Figure 5 Biocompatibility test diagram of magnetic hydrogel microspheres loaded with MSC cells provided in the examples of this application:

[0023] (A) is an optical microscope observation of magnetic hydrogel microspheres loaded with MSC cells on the 1st, 3rd, 5th and 7th day of culture; (B) is a cytoskeleton and nucleus staining image of magnetic hydrogel microspheres loaded with MSC cells on the 7th day of culture; (C) is a live-dead staining experiment image of magnetic hydrogel microspheres loaded with MSC cells; (D) is a cell survival rate analysis image of loaded MSC cells on the 1st, 4th and 7th day;

[0024] Figure 6 The degradation and recovery test diagram of magnetic hydrogel microspheres and magnetic materials provided in the embodiments of the present application:

[0025] (A) is an optical microscope observation image of magnetic hydrogel microspheres; (B) is an optical microscope observation image of magnetic hydrogel microspheres treated with GelMA lyase; (C) is an optical microscope observation image of the movement of magnetic materials in magnetic hydrogel microspheres under the action of an external magnetic field;

[0026] Figure 7 The magnetic hydrogel microspheres loaded with MSC cells provided in the embodiments of the present application are:

[0027] (A) is the staining image of the cytoskeleton and nucleus of the bone defect area after the cells in the bone defect area were acted on by magnetic hydrogel microspheres loaded with MSC cells; (B) is the optical microscopic observation image of the cells in the bone defect area on days 1, 5, 10, and 14 after the cells in the bone defect area were cultured for osteogenic differentiation; (C) is the ALP staining image and ARS staining image of the cells in the bone defect area on days 7 and 14 after the cells in the bone defect area were cultured for osteogenic differentiation. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0029] It should be noted that if there are descriptions involving "first", "second", etc. in the implementation of this application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance and implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in the field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0030] See also Figure 1 The embodiment of the present application provides a magnetic hydrogel microsphere comprising: a hydrogel and a magnetic material, wherein the hydrogel is in a sphere or an ellipsoid, and the magnetic material is in a spiral structure. The hydrogel and the magnetic material form a core-shell structure, and the hydrogel completely covers the magnetic material.

[0031] The hydrogel has good biocompatibility and degradability. When the magnetic hydrogel microspheres carry effective substances, such as cells, the cells can be adsorbed on the surface of the magnetic hydrogel microspheres, and the cells can be released when the hydrogel is degraded.

[0032] The magnetic material structure in the magnetic hydrogel microspheres in the prior art is relatively simple, and may not produce an effective motion mode under an external magnetic field. In an environment with a low Reynolds number (Re number) (such as in vivo or in a microfluidic system), the problem of excessive fluid resistance will be faced. After the hydrogel is degraded, the magnetic material may not be effectively recovered. The magnetic material in the magnetic hydrogel microspheres in the embodiments of the present application is a spiral structure, which has better fluid mechanics properties and can effectively overcome fluid resistance through rotational motion, thereby enabling more precise orientation and navigation, which is conducive to the movement of the magnetic hydrogel microspheres to the target area to achieve accurate release of the effective substances carried, and can also effectively recover the magnetic material, avoiding the long-term residue of the magnetic material in the body and reducing potential biosafety risks.

[0033] In some embodiments, the hydrogel includes at least one of gelatin methacryloyl gelatin (GelMA), polyethylene glycol diacrylate (PEGDA), polyethylene glycol diacrylamide (PEGDMA), hyaluronic acid methacrylate (HAMA).

[0034] Hydrogel has good biocompatibility and degradability. When magnetic hydrogel microspheres are used for targeted transport, the hydrogel can be degraded in the target area to accurately release the effective substances carried by the magnetic hydrogel microspheres. Preferably, the hydrogel is GelMA, which has unique physical and chemical properties, is suitable for fields such as cell therapy and tissue engineering, and has excellent biocompatibility and degradability.

[0035] In some embodiments, the magnetic material includes at least one of metal oxide nanoparticles and magnetic polymers, and the metal oxide nanoparticles include at least one of ferrosoferric oxide nanoparticles, cobalt oxide nanoparticles, and manganese oxide nanoparticles.

[0036] In some embodiments, the present invention also provides a method for preparing magnetic hydrogel microspheres as described above in the present invention, comprising the steps of:

[0037] S1, providing a core layer solution, a shell layer solution and an oil phase solution;

[0038] S2. Inject the core layer solution, shell layer solution and oil phase solution into different flow channels of the coaxial flow microfluidic device respectively to prepare monomer droplets, and use ultraviolet light to cure the monomer droplets to obtain magnetic hydrogel microspheres.

[0039] In some embodiments, the core layer solution includes 1-2% sodium cellulose, 1-5% polyethylene glycol diacrylate, 0.1-0.3% photoinitiator and 1.5-3% magnetic material by mass percentage. For example, in the core layer solution, the mass percentage of sodium cellulose is 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8% or 2%, etc.; the mass percentage of polyethylene glycol diacrylate is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.; the mass percentage of photoinitiator is 0.1%, 0.15%, 0.2%, 0.25% or 0.3%, etc.; the mass percentage of magnetic material is 1.5%, 2%, 2.5% or 3%, etc. Among them, sodium cellulose as a thickener can increase the viscosity of the core layer solution, which is conducive to the formation of an internal spiral structure, and the cross-linking effect of polyethylene glycol diacrylate can encapsulate the magnetic substance in the spiral structure.

[0040] The core layer solution is prepared by dissolving polyethylene glycol diacrylate (PEGDA), sodium cellulose, and a photoinitiator in a phosphate buffer solution (PBS buffer), then adding a magnetic material, and mixing them evenly to obtain a core layer solution. The shell layer solution is prepared by dissolving a hydrogel, sodium cellulose, and a photoinitiator in a PBS buffer solution to obtain a shell layer solution.

[0041] In some embodiments, the shell layer solution includes 5-10% hydrogel, 0.3-0.5% sodium cellulose, and 0.2-0.4% photoinitiator by weight. For example, in the shell layer solution, the mass percentage of hydrogel is 5%, 6%, 7%, 8%, 9%, or 10%, etc.; the mass percentage of sodium cellulose is 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%, etc.; the mass percentage of photoinitiator is 0.2%, 0.25%, 0.3%, 0.35%, or 0.4%, etc. Sodium cellulose can provide a certain viscosity for the core layer solution, and the photoinitiator can initiate the polymerization, cross-linking, and curing of the monomers in the subsequent preparation process.

[0042] In some embodiments, the oil phase solution includes at least one of mineral oil, silicone oil, liquid paraffin, fluorinated oil, olive oil, corn oil, and soybean oil.

[0043] In some embodiments, the photoinitiator includes at least one of lithium phenyl-2,4,6-trimethylbenzoyl phosphate (photoinitiator LAP), Irgacure 2959, and Riboflavin.

[0044] In some embodiments, see Figure 2In S2, the core layer solution, shell layer solution and oil phase solution are respectively injected into different flow channels of the coaxial flow microfluidic device. The core layer solution, shell layer solution and oil phase solution converge at the liquid outlet of the coaxial flow microfluidic device. When the high viscosity core layer solution meets the low viscosity shell layer solution, the viscous stress of the shell layer solution acts on the core layer solution, causing the core layer solution to no longer expand, bend and form a twisted channel, and produce a spiral state. The core layer solution in a spiral state (helical structure) is emulsified in the coaxial flow microfluidic device under the coating of the oil phase solution to form monomer droplets through oil-in-water emulsification, and the monomer droplets are then cross-linked and cured by ultraviolet light, so that the obtained magnetic hydrogel microspheres finally retain a unique internal structure, that is, the internal magnetic material with a spiral structure and the external hydrogel form a core-shell structure.

[0045] In some embodiments, the structure of the coaxial flow microfluidic device is as follows Figure 3 As shown, there are three liquid injection ports and one liquid outlet, the core solution is injected from the core solution injection port (Inlet for inner flow), the shell solution is injected from the shell solution injection port (Inlet for outer flow), and the oil phase solution is injected from the oil phase solution injection port (Inlet for oilphase). The prepared magnetic hydrogel microspheres flow out from the liquid outlet (Outlet).

[0046] In some embodiments, the injection flow rate of the core layer solution is 2-10 μL / min, for example, the injection flow rate of the core layer solution is 2 μL / min, 3 μL / min, 4 μL / min, 5 μL / min, 6 μL / min, 7 μL / min, 8 μL / min, 9 μL / min or 10 μL / min, etc. The injection flow rate of the shell layer solution is 6-20 μL / min, for example, the injection flow rate of the shell layer solution is 6 μL / min, 8 μL / min, 10 μL / min, 12 μL / min, 14 μL / min, 16 μL / min, 18 μL / min or 20 μL / min, etc. The injection flow rate of the oil phase solution is 0.6-2.5 mL / min, for example, 0.6 mL / min, 0.8 mL / min, 1 mL / min, 1.2 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.8 mL / min, 2 mL / min, 2.2 mL / min, 2.4 mL / min or 2.5 mL / min, etc.

[0047] By controlling the injection speed of the core solution, shell solution and oil phase solution, the helical structure of the magnetic material is formed by taking advantage of the difference in viscosity between the core solution and the shell solution and the folding instability in fluid dynamics, and then under the action of the oil phase solution, monomer droplets are obtained through oil-in-water emulsification.

[0048] In some embodiments, the UV light intensity of the UV curing is 60-110 mW / cm 2 For example, the UV light intensity of UV curing is 60mW / cm 2 、70mW / cm 2 、80mW / cm 2 、90mW / cm 2 , 100mW / cm 2 or 110mW / cm 2 By controlling the intensity of ultraviolet light, the photoinitiator in the monomer droplets can be activated, cross-linked and cured, and the complex structure in the monomer droplets can be retained to form magnetic hydrogel microspheres.

[0049] The present application also provides an application of the magnetic hydrogel microspheres described above in the present application in the preparation of targeted transport products, wherein the targeted transport products are used to transport cells (cell delivery) or active ingredients such as drugs.

[0050] For example, see Figure 4 When the magnetic hydrogel microparticles in the embodiment of the present application are used to load mesenchymal stem cells (MSC), the MSC cells are attached to the surface or inside of the magnetic hydrogel microspheres to form a cell-microsphere complex. Under the guidance and manipulation of the external magnetic field, the magnetic hydrogel microspheres loaded with MCS cells are accurately delivered to the damaged bone loss area. Since the magnetic material with a spiral structure inside the magnetic hydrogel microspheres can respond to the external magnetic field, the magnetic hydrogel microspheres loaded with MCS cells are highly controllable and can effectively reach and concentrate on the damaged area.

[0051] When the magnetic hydrogel microspheres loaded with MCS cells reach the bone loss area, the hydrogel therein begins to gradually degrade. As the hydrogel degrades, the loaded MSC cells are released and locally distributed at the site of injury. Subsequently, under the influence of the injury microenvironment, the MSC cells begin to differentiate, ultimately promoting the formation of new bone tissue and the repair of the defect area. At the same time, as the hydrogel degrades, the magnetic materials with a helical structure originally present inside the magnetic hydrogel microspheres are gradually exposed. Since these magnetic materials still retain their magnetism, they can be captured and recovered again by the external magnetic field.

[0052] The above process not only completes the delivery and local repair of cells, but also makes it possible to recycle the magnetic material, ensuring the reusability and cell compatibility of the system. By loading MSC cells with the magnetic hydrogel microspheres of the embodiment of the present application, effective delivery of MSC cells and bone defect repair are achieved.

[0053] The following will provide further explanation through specific implementation methods.

[0054] Example 1

[0055] (1) 1% polyethylene glycol diacrylate (PEGDA), 1% sodium cellulose and 0.1% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonate lithium) were dissolved in PBS buffer, and then 1.5% ferrosoferric oxide (FeO) nanoparticles were added to prepare the core layer solution. 8% gelatin methacryloyl (GelMA) hydrogel, 0.4% sodium cellulose and 0.25% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonate lithium) were dissolved in PBS buffer to prepare the shell layer solution. Corn oil was used as the oil phase solution.

[0056] (2) The core layer solution, shell layer solution and oil phase solution in (1) are respectively injected into the corresponding injection ports of the coaxial flow microfluidic device in the embodiment of the present application, and the injection flow rate of the core layer solution is controlled to be 6 μL / min, the injection flow rate of the shell layer solution is controlled to be 13 μL / min, the injection flow rate of the oil phase solution is controlled to be 1.5 mL / min, and the irradiation intensity of the ultraviolet light is controlled to be 80 mW / cm 2 , magnetic hydrogel microspheres were prepared.

[0057] Example 2

[0058] (1) 3% polyethylene glycol diacrylate (PEGDA), 1.5% sodium cellulose and 0.2% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium) were dissolved in PBS buffer, and then 2% ferrosoferric oxide (FeO ) nanoparticles were added to prepare the core layer solution. 5% gelatin methacryloyl (GelMA) hydrogel, 0.3% sodium cellulose and 0.2% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium) (alternative) were dissolved in PBS buffer to prepare the shell layer solution. Soybean oil was used as the oil phase solution.

[0059] (2) The core layer solution, shell layer solution and oil phase solution in (1) are respectively injected into the corresponding injection ports of the coaxial flow microfluidic device in the embodiment of the present application, and the injection flow rate of the core layer solution is controlled to be 2 μL / min, the injection flow rate of the shell layer solution is controlled to be 6 μL / min, the injection flow rate of the oil phase solution is controlled to be 0.6 mL / min, and the irradiation intensity of the ultraviolet light is controlled to be 60 mW / cm 2 , magnetic hydrogel microspheres were prepared.

[0060] Example 3

[0061] (1) Solution preparation. 5% polyethylene glycol diacrylate (PEGDA), 1% sodium cellulose and 2% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonate lithium) (alternative) were dissolved in PBS buffer, and then 3% ferrosoferric oxide (FeO) nanoparticles were added to prepare the core layer solution. 10% gelatin methacryloyl (GelMA) hydrogel, 0.5% sodium cellulose and 0.4% photoinitiator LAP (phenyl-2,4,6-trimethylbenzoylphosphonate lithium) were dissolved in PBS buffer to prepare the shell layer solution. Silicone oil was used as the oil phase solution.

[0062] (2) The core layer solution, shell layer solution and oil phase solution in (1) are respectively injected into the corresponding injection ports of the coaxial flow microfluidic device in the embodiment of the present application, and the injection flow rate of the core layer solution is controlled to be 10 μL / min, the injection flow rate of the shell layer solution is controlled to be 20 μL / min, the injection flow rate of the oil phase solution is controlled to be 2.5 mL / min, and the irradiation intensity of the ultraviolet light is controlled to be 110 mW / cm 2 , magnetic hydrogel microspheres were prepared.

[0063] Example 4

[0064] The magnetic hydrogel microspheres prepared in Example 1 were co-cultured with MSC cells. About 1000 magnetic hydrogel microspheres were first added to a 48-well culture plate, followed by the addition of cells at a density of 5×10 5 After culturing for 24 hours at 5% CO2 and 37°C, the MSC cells adhered to the surface of the magnetic hydrogel microspheres, and the magnetic hydrogel microspheres loaded with MSC cells were obtained. The cell culture medium used was iCell primary mesenchymal stem cell culture system (PriMed-iCell-012, iCell Bioscience, Ltd., China).

[0065] Test Example 1

[0066] In the field of regenerative medicine and tissue engineering, the biocompatibility of materials is a key factor in evaluating their potential for clinical application. As an emerging cell carrier and drug delivery system, magnetic hydrogel microspheres have good operability and targeting, but their biocompatibility needs to be evaluated to ensure their safety and effectiveness. This test case tests the biocompatibility of magnetic hydrogel microspheres in an in vitro environment.

[0067] The magnetic hydrogel microspheres loaded with MSC cells prepared in Example 4 were transferred to fresh culture medium for continued culture, and samples were taken on the 1st, 3rd, 5th and 7th days and observed using an optical microscope. Figure 5 As shown in (A), from Figure 5 As can be seen in (A), starting from the first day, a small number of MSC cells attached to the microgel surface, and then on the third and fifth days, the number of cells increased significantly, and on the seventh day, almost covered the entire magnetic hydrogel microsphere, indicating that the attachment and expansion of MSC cells on the magnetic hydrogel microspheres gradually increased with time, which further indicates that the magnetic hydrogel microspheres in the embodiments of the present application can promote cell proliferation and have the potential to be used as cell carriers.

[0068] The magnetic hydrogel microspheres loaded with MSC cells cultured for 7 days were tested for cytoskeleton (F-actin) and cell nucleus DAPI staining. The test results are as follows: Figure 5 As shown in (B). Figure 5 In (B), it can be seen that MSC cells are evenly distributed on the surface of magnetic hydrogel microspheres, forming a complete cell network structure and showing good interconnectivity. This shows that magnetic hydrogel microspheres not only support cell attachment and growth, but also promote cell-to-cell interactions and maintain the normal morphology and function of cells. This further shows that magnetic hydrogel microspheres have a good supporting effect on MSC cells, providing a strong foundation for subsequent cell delivery and tissue repair applications.

[0069] The magnetic hydrogel microspheres loaded with MSC cells cultured for 7 days were used to perform live and dead cell staining analysis on the attached MSC cells. The results are as follows: Figure 5 As shown in (C). Figure 5 As can be seen in (C), more than 90% of MSC cells survive on the magnetic hydrogel microspheres, indicating that the magnetic hydrogel microspheres have extremely high biocompatibility.

[0070] The magnetic hydrogel microspheres loaded with MSC cells were taken on the 1st, 4th and 7th day of culture, and the attached MSC cells were stained for live and dead cells, and the survival rate of the attached MSC cells was counted. The results are as follows: Figure 5 As shown in (D). Figure 5 As can be seen in (D), as time goes by, although the density of attached MSC cells increases, the survival rate of MSC cells remains at a high level, which also shows that the magnetic hydrogel microspheres in the examples of the present application have the potential to be used as cell carriers.

[0071] Test Example 2

[0072] The magnetic hydrogel microspheres prepared in Example 1 were subjected to degradation and magnetic material recovery tests in an in vitro environment. GelMA hydrogel was degraded at 37°C using GelMA lysis solution (EFL-GM-LS-001, EFL, China). A 0.3 mg / mL working solution was prepared using complete cell culture medium. After adding the working solution that can immerse the magnetic hydrogel microspheres, the magnetic hydrogel microspheres were fully contacted with the lysis working solution. Aseptically lysed in a 37°C incubator, the lysis was observed under a microscope every 15 minutes. After complete biodegradation, the magnetic helical structure was recovered using an external magnetic field. The results are as follows. Figure 6 As shown in (A)-(C). Figure 6 As can be seen in (A), the magnetic hydrogel microspheres have a distinct core-shell structure, in which the hydrogel completely covers the magnetic material. Figure 6 As can be seen in (B), after the magnetic hydrogel microspheres were treated with GelMA lyase, the hydrogel in the magnetic hydrogel microspheres was degraded, and the magnetic material with a spiral structure inside was exposed. Figure 6 It can be seen from (C) that under the action of the external magnetic field, the free magnetic material is adsorbed and aggregated by the magnetic field, and the magnetic material can be transferred as the external magnetic field moves. Combined with the results of Test Example 2, it can be seen that the magnetic hydrogel microspheres in the embodiment of the present application achieve efficient delivery, safe degradation and recovery of magnetic materials, overcome the common material residues and safety hazards in the prior art, and provide reliable guarantees for further applications in the biomedical field.

[0073] Test Example 3

[0074] The magnetic hydrogel microspheres loaded with MSCs were extracted from the culture medium and delivered to the target area using an external magnetic field. After delivery, the magnetic hydrogel microspheres degraded, releasing the MSCs that adhered to the target location and proliferated. The cells were washed twice with sterile PBS to remove any residual culture medium and then fixed in 4% paraformaldehyde (BL539A, Biosharp) for 15 minutes. After fixation, the cells were washed twice with sterile PBS for 3 minutes each time.

[0075] Prepare BCIP / NBT alkaline phosphatase staining solution according to the instructions and add it to MSCs for ALP staining. The reaction is carried out in the dark for 30 min. Afterwards, remove the BCIP / NBT staining solution and wash the MSCs twice with deionized water to stop the staining reaction.

[0076] For ARS staining, after fixation with 4% paraformaldehyde, Alizarin Red S staining solution (0.2%, pH 8.3, Solarbio, G1450) was added and incubated at room temperature for 30 min. Finally, the Alizarin Red S staining solution was removed and the MSCs were washed twice with deionized water to terminate the staining reaction. The results are shown in Figure 7 As shown. Figure 7 As can be seen in (A), after the loaded MSC cells are delivered to the target area, the cells adhere and grow in the target area as the microgel degrades. Figure 7 As can be seen in (B), the osteoblasts growing in the bone injury area differentiate significantly over time, which further indicates that the loaded MSC cells can promote the osteogenic differentiation of cells in the bone injury area. Figure 7 As can be seen in (C), by comparing the ALP staining and ARS staining of the cells growing in the bone injury area on the 7th day and the 14th day, the differentiation state and osteogenic activity of the osteoblasts growing in the bone injury area on the 14th day were significantly improved, and the degree of calcification and mineralization in the extracellular matrix of the osteoblasts growing in the bone injury area on the 14th day were also significantly increased.

[0077] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A magnetic hydrogel microsphere, characterized in that: The magnetic hydrogel microspheres include hydrogel and magnetic material. The hydrogel is in a sphere or ellipsoid shape, and the magnetic material is in a spiral structure. The hydrogel and the magnetic material form a core-shell structure, and the hydrogel completely covers the magnetic material.

2. The magnetic hydrogel microspheres according to claim 1, characterized in that: The hydrogel comprises at least one of gelatin methacrylated gelatin, polyethylene glycol diacrylate, polyethylene glycol diacrylamide, and hyaluronic acid methacrylate.

3. The magnetic hydrogel microspheres according to claim 1, characterized in that: The magnetic material includes at least one of magnetic metal oxide nanoparticles and magnetic polymers; The magnetic metal oxide nanoparticles include at least one of ferroferric oxide nanoparticles, cobalt oxide nanoparticles, and manganese oxide nanoparticles.

4. A method for preparing magnetic hydrogel microspheres according to any one of claims 1 to 3, characterized in that: Includes steps: Providing a core layer solution, a shell layer solution and an oil phase solution, wherein the core layer solution includes a magnetic material, and the shell layer solution includes a hydrogel; The core layer solution, the shell layer solution and the oil phase solution are respectively injected into different flow channels of the coaxial flow microfluidic device, the core layer solution, the shell layer solution and the oil phase solution converge at the liquid outlet of the coaxial flow microfluidic device to obtain monomer droplets, and the monomer droplets are cured using ultraviolet light to obtain the magnetic hydrogel microspheres.

5. The method for preparing magnetic hydrogel microspheres according to claim 4, characterized in that: In terms of mass percentage, the core layer solution includes 1-2% sodium cellulose, 1-5% polyethylene glycol diacrylate, 0.1-0.3% photoinitiator and 1.5-3% magnetic material; In terms of mass percentage, the shell solution includes 5-10% of the hydrogel, 0.3-0.5% of sodium cellulose, and 0.2-0.4% of a photoinitiator; The oil phase solution includes at least one of mineral oil, silicone oil, liquid paraffin, fluorinated oil, olive oil, corn oil, and soybean oil.

6. The method for preparing magnetic hydrogel microspheres according to claim 5, characterized in that: The photoinitiator includes at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphate, Irgacure 2959, and riboflavin.

7. The method for preparing magnetic hydrogel microspheres according to claim 5, characterized in that: The core layer solution, shell layer solution and oil phase solution are respectively injected into different flow channels of the coaxial flow microfluidic device, the injection flow rate of the core layer solution is 2-10 μL / min, the injection flow rate of the shell layer solution is 6-20 μL / min, and the injection flow rate of the oil phase solution is 0.6-2.5 mL / min.

8. The method for preparing magnetic hydrogel microspheres according to claim 5, characterized in that: The UV curing has an UV irradiation intensity of 60-110 mW / cm 2 .

9. Use of the magnetic hydrogel microspheres according to any one of claims 1 to 3 in the preparation of targeted transport products.

10. The use according to claim 9, characterized in that: The targeted transport product is used to transport cells or drugs.

Citation Information

Patent Citations

  • Preparation method and application of porous hydrogel microspheres based on droplet microfluidic technology

    CN118846972A